Bridging the Divide: Human Resource Challenges in the Education Sector of Developing Nation - Harmita; Silvia Marniati; M Nasruddin; Muazza; Aprillitzavivayarti (Al-Qalam Institue, 2025)
Human resource (HR) management in Indonesia’s education sector continues to face persistent challenges that directly influence the quality of national education. This study aims to analyze problems related to employment disparities between civil servant (PNS) and honorary teachers, unequal teacher distribution, recruitment quality, and welfare issues in educational institutions. Using a literature review method, the research synthesizes data from books, academic journals, and official government documents to identify key patterns and policy gaps. The results show that disparities in employment status create inequality in job security and motivation, while recruitment and placement often fail to reflect competency-based standards. Moreover, inadequate welfare and professional development opportunities significantly affect teacher satisfaction and performance. Therefore, this study emphasizes the need for comprehensive HR reforms in education to ensure equity, professionalism, and sustainable development among educators.